Impact of surface treatment on the mechanical properties of sisal and jute reinforced with epoxy resin natural fiber hybrid composites - A. Arun Premnath (Journal of Natural Fibers, 2019)
Natural fiber composites (NFCs) are gaining importance in various fields of engineering due to their ecofriendly nature and low cost. The present work is aimed in studying the mechanical properties such as tensile strength, flexural strength, impact strength, and hardness for natural fiber/epoxy resin composites reinforced with sisal and jute. The composites are prepared by hand lay-up method by varying the proportion of jute fiber. One set of fibers is surface treated with NAOH solution and its impact on mechanical strength was studied. From the results obtained, it was observed that the tensile strength increases by 20%, flexural strength by 25%, impact strength increases by 27.27%, and hardness by 5% for surface treated composites. Scanning electron microscope was used to study the morphology of prepared specimen and fractured specimen. The results indicate that surface-treated composites perform better than the untreated fiber composites.